Aplikasi Matematika Dalam Pengaturan Berat Badan Dengan Menghitung Kalori Dan Menggunakan Sistem Body Mass Index (BMI) - Hernawati, Dewi (Department of Mathematics Education Program IPI Garut, 2012)
The number of foods from each group must be balanced, balanced diet is a diet that contains a source of energy (carbohydrates and fats), builders and other sources regulator suitable for the needs of each person. The number of calories needed depends on the type of work, age, gender, physical condition (healthy / ill), weight loss and climate. The heavier the work or activities of more and more food is needed. By counting calories required to use the system and body by BMI (body mass index) can control our body to maintain good health because of the calorie count and know their BMI. It may reduce the risk of various diseases such as cardiovascular, diabetes, hypertension, dyslipidemia, fatty liver, osteoarthritis. The World Health Organization (WHO) decided BMI of less than 18.5 as underweight and may indicate malnutrition, BMI 25-29 should be considered overweight and a BMI over 30 is obese.